Vaccines for healthcare associated infections without vaccine prevention to date. (August 2022) - Amandine, Gagneux-Brunon; Gagnaire, Julie; Pelissier, Carole; Philippe, Berthelot; Elisabeth, Botelho-Nevers
Abstract: In spite of the widespread implementation of preventive strategies, the prevalence of healthcare-associated infections (HAIs) remains high. The prevalence of multidrug resistant organisms is high in HAIs. In 2019, the World Health Organization retained antimicrobial resistance as one of the ten issues for global health. The development of vaccines may contribute to the fight against antimicrobial resistance to reduce the burden of HAIs. Staphylococcus aureus, Gram negative bacteria and Clostridium difficile are the most frequent pathogens reported in HAIs. Consequently, the development of vaccines against these pathogens is crucial. At this stage, the goal of obtaining effective vaccines against S.aureus and Gram negative bacteria has not yet been achieved. However, we can expect in the near future availability of a vaccine against C. difficile . In addition, identifying populations who may benefit from these vaccines is complex, as at-risk patients are not great responders to vaccines, or as vaccination may occur too late, when they are already confronted to the risk. Vaccinating healthcare workers (HCWs) against these pathogens may have an impact only if HCWs play a role in the transmission and in the pathogens acquisition in patients, if the vaccine is effective to reduce pathogens carriage and if vaccine coverage is sufficient to protect patients. Acceptance of these potential vaccines should be evaluated and addressed in patients and in HCWs.